Web-Based Task Notification System and Employee Performance Results Storage - Wardani, Syahrillah Rahma; Sufaidah, Siti; Airlangga, Primaadi (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Significant developments in information technology have led to changes in people's mindsets and lifestyles. This also affects the performance of agencies including universities. the results of observations and interviews conducted at Unwaha show that the storage of employee work results is still manual which risks losing data, besides that there is no notification of employee assignments so that employees tend to experience difficulties in carrying out tasks.Therefore it is necessary to develop an information system for notification of tasks and storing employee work results to prevent data loss. information system development was carried out using the waterfall method from April to August 2022 at KH A. Wahab Hasbullah University, Jombang. The research results show that the information system developed makes it easier for employees to report work assignments, makes it easier for employees to receive additional assignments, can manage and store all assignment data from employees, and helps shorten the time in the process of reporting employee work assignments.